Bagaimana peran kepuasan dan stres kerja pada turnover intention karyawan? - Ramadhan, Rizal Dwiki; Mulyadi, Hari; Tarmedi, Eded (Journal of Business Management Education (JBME), 2019)
The purpose of the study was to determine the effect of job satisfaction on turnover intention, work stress on turnover intention, job satisfaction and work stress on turnover intention. The object that becomes the unit of analysis in this study is the employee of the production section in the textile industry. The type of research used is descriptive with the method used is explanatory survey with a sample of 107 respondents. The results of this study found that the effect of job satisfaction on turnover intention was included in the medium category. Job stress has an effect on employee turnover intention. Job satisfaction and work stress have an effect on the turnover intention of PT X textile industry employees. In this study it was found if the condition of job satisfaction is good, it will reduce the turnover rate of employee intention. In addition, if the work stress level is low, then the turnover of the intention of the textile industry employees will be low.